Analysis of Sub-sectors of Processing Industry in Banggai Re-gency Indonesia using Local Superior Products - Layoo, Nurhidayah; Rahman, Wahyudin; K. Djawa, Sutrisno; Latuba, Jurtan; Mambuhu, Nurmawati; Moridu, Irwan; Hadiyati, Rini; H Possumah, Nurcahya; Mina, Risno; Kurniasih, Nuning (International Journal of Engineering and Technology, 2018)
The purpose ofÂ this research was to determine superior local products in the sub-sector of the processing industry of Banggai Regency Indonesia by using Analytic Hierarchy Process (AHP) approach.. The research was conducted based on several criteria such as the production facility, market potential, human resource support, uniqueness, and economic contribution. The data were taken by purposive sampling method by considering the capacity and ability of respondents to provide the necessary data, here the respondents consisted of 15 SMEs stakeholders, and the expert stakeholders of 4 heads of division in Industry and Trade Department, 4 heads of division in Cooperative and SMEs, 7 academics in Faculty of Industry Technic, and 5 in Faculty of Economics. The data were collected through Focus Group Discussion (FGD), questioner, and in-depth interview. The result shows that the superior local products of Banggai RegencyÂ in the processing industry sub-sector are processed food and beverage products, with an emphasis on SME empowerment located in aspects of human resources, production facilities and utilization of market potential.Â